The Impact of Transnational Education in Receiving Countries - Knight, Jane; McNamara, John (International Higher Education, 2015)
Most research on TNE examines issues from the sending or providing country. This article reports on the impacts of TNE from the receiving or host country perspective. Topics addressed include motivation, costs, benefits, awareness levels, student profile and future outlook of TNE.